2011
DOI: 10.4314/gab.v9i2.72184
|View full text |Cite
|
Sign up to set email alerts
|

Loss of learning space within a legally inclusive education system: institutional responsiveness to mainstreaming of pregnant learners in formal education

Abstract: This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Thus, students tend to depend on the teacher for information. Participants only considered distance learning when they are out of school due to expulsion (Runhare, 2010). The other issue with distance learning is that there is need to use computers and internet, and in Zimbabwe these are not easily accessible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, students tend to depend on the teacher for information. Participants only considered distance learning when they are out of school due to expulsion (Runhare, 2010). The other issue with distance learning is that there is need to use computers and internet, and in Zimbabwe these are not easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Zimbabwean learners who get pregnant have a right to continue with their education (Runhare, 2010). However research has found that some girls who became pregnant prefer to suspend their schooling or transfer to another school after delivery (Runhare, 2010) because pregnant learners are often treated as bad influences on others and are looked down upon. If distance learning were available, learners who become pregnant could enroll for online education or other formats and continue with their education.…”
Section: Distance Learning In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Runhare (2010) and Odu, Ayodele and Isola (2015) revealed that it can be difficult for a young mother to return to school because both the school and community fear that young mothers may become a bad influence to other learners in the school. It is against such negative perceptions to teen motherhood that in most of the Sub-Saharan African region, while policies that allow pregnant schoolgirls to either continue with or return to school after giving birth, most of them would rather voluntarily drop out of school due to the stigma attached to teenage pregnancy (Chigona & Chetty, 2008;Runhare, 2010;Runhare & Hwami, 2014). In South Africa, Chigona and Chetty (2008) and Grant and Hallman (2006) observed that a supportive family environment is a key determinant factor for pregnant or parenting schoolgirls' decision to continue with their education.…”
Section: Negative Societal Attitudes and Stigma Towards Pplsmentioning
confidence: 99%
“…There is still a lot to be gained by current South African policy on preventing school dropout and alcohol and tobacco use. Currently, South African policies preventing school dropout include permitting the re-enrolment of pregnant learners (114) and exempting students who do not have the affordability from paying tuition fees (115). National policies on anti-tobacco and alcohol include prohibiting the sale of these substances to minors and increased taxes on cigarettes and alcoholic beverages.…”
Section: Practical Implicationsmentioning
confidence: 99%